2018
DOI: 10.1016/j.cell.2018.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Levels Selectively Regulate Translation and Lineage Commitment in Human Hematopoiesis

Abstract: SUMMARY Blood cell formation is classically thought to occur through a hierarchical differentiation process, although recent studies have shown that lineage commitment may occur earlier in hematopoietic stem and progenitor cells (HSPCs). The relevance to human blood diseases and the underlying regulation of these refined models remain poorly understood. By studying a genetic blood disorder, Diamond-Blackfan anemia (DBA), where the majority of mutations affect ribosomal proteins and the erythroid lineage is sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
407
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(436 citation statements)
references
References 60 publications
(125 reference statements)
27
407
2
Order By: Relevance
“…Recent studies at the single cell level have also provided renewed insight as to GATA1 protein expression in human erythropoiesis, from hematopoietic stem and progenitor cells (HSPCs) to terminally differentiated erythroid cells. In one study, GATA1 protein could be detected at low levels in a subset of HSPCs, gradually increasing as cells differentiate, reaching high levels in lineage committed erythroid cells . Similarly, in another study, GATA1 protein was clearly detectable at the CMP stage and gradually increased with cell commitment and differentiation through the CFU‐E, proerythroblast, and basophilic erythroblast and orthochromatic erythroblast stages .…”
Section: Gata1 Expression In Hematopoiesismentioning
confidence: 90%
“…Recent studies at the single cell level have also provided renewed insight as to GATA1 protein expression in human erythropoiesis, from hematopoietic stem and progenitor cells (HSPCs) to terminally differentiated erythroid cells. In one study, GATA1 protein could be detected at low levels in a subset of HSPCs, gradually increasing as cells differentiate, reaching high levels in lineage committed erythroid cells . Similarly, in another study, GATA1 protein was clearly detectable at the CMP stage and gradually increased with cell commitment and differentiation through the CFU‐E, proerythroblast, and basophilic erythroblast and orthochromatic erythroblast stages .…”
Section: Gata1 Expression In Hematopoiesismentioning
confidence: 90%
“…However, how the changes in the ribosome machinery in DBA selectively impairs erythropoiesis has been unclear. Recent work by the Sankaran laboratory revealed that transcripts with shorter 5′‐UTR, which are predicted to have less complex secondary structure and fewer upstream start codons (uAUGs), are more sensitive to ribosome protein haploinsufficiency . Significantly longer 5′ UTR lengths and more complex 5′‐UTR structures were found in most hematopoietic master regulators compared to the group of transcripts showing sensitivity to ribosomal protein haploinsufficiency .…”
Section: Gata1 Mutations In Dbamentioning
confidence: 99%
“…Recent work by the Sankaran laboratory revealed that transcripts with shorter 5′‐UTR, which are predicted to have less complex secondary structure and fewer upstream start codons (uAUGs), are more sensitive to ribosome protein haploinsufficiency . Significantly longer 5′ UTR lengths and more complex 5′‐UTR structures were found in most hematopoietic master regulators compared to the group of transcripts showing sensitivity to ribosomal protein haploinsufficiency . Intriguingly, although GATA1 has a relative short and unstructured 5′‐UTR, it exhibits unique features among hematopoietic transcriptional regulators, which may give GATA1 mRNA a higher translation efficiency but make it more sensitive to RP haploinsufficiency in DBA patients …”
Section: Gata1 Mutations In Dbamentioning
confidence: 99%
See 1 more Smart Citation
“…WES of patients who had a clinical diagnosis of DBA, but no known pathogenic mutations, revealed mutations impairing the production of GATA1 in several patients (Sankaran et al , ; Ludwig et al , ). Building upon this knowledge, subsequent functional studies solidified the link between RPs, GATA1, and defects in erythropoiesis by showing that RP haploinsufficiency reduces ribosome levels and thus results in reduced GATA1 mRNA translation (Ludwig et al , ; Khajuria et al , ). Therefore, DBA genetics revealed new information about the regulation of GATA1 expression in human hematopoiesis, establishing a novel link between ribosome levels and GATA1 driven by its high translation rate (Khajuria et al , ).…”
Section: Introductionmentioning
confidence: 99%